2019
DOI: 10.1101/811430
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Representation of Visual Landmarks in Retrosplenial Cortex

Abstract: 8The process by which visual information is incorporated into the brain's spatial framework 9to represent landmarks is poorly understood. Studies in humans and rodents suggest that 10 retrosplenial cortex (RSC) plays a key role in these computations. We developed an RSC-11 dependent behavioral task in which head-fixed mice learned the spatial relationship 12 between visual landmark cues and hidden reward locations. Two-photon imaging 13revealed that these cues served as dominant reference points for most task-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 86 publications
6
62
1
Order By: Relevance
“…In addition, all areas gave stronger responses during active behavior than during passive viewing. This influence may reach visual cortex through retrosplenial cortex (Makino and Komiyama, 2015), an area that contains experience-dependent spatial signals (Mao et al, 2017(Mao et al, , 2018 and is more strongly modulated by active navigation than V1 (Fischer et al, 2020). Another candidate is anterior cingulate cortex (Zhang et al, 2014), whose dense projections to V1 carry signals related to locomotion (Leinweber et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all areas gave stronger responses during active behavior than during passive viewing. This influence may reach visual cortex through retrosplenial cortex (Makino and Komiyama, 2015), an area that contains experience-dependent spatial signals (Mao et al, 2017(Mao et al, , 2018 and is more strongly modulated by active navigation than V1 (Fischer et al, 2020). Another candidate is anterior cingulate cortex (Zhang et al, 2014), whose dense projections to V1 carry signals related to locomotion (Leinweber et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that subsets of RSC neurons are tuned to allocentric and egocentric spatial variables including position (Alexander and Nitz, 2015;Mao et al, 2017Mao et al, , 2018, head direction (Chen et al, 1994;Clark et al, 2010;Jacob et al, 2017), proximity to landmarks (Alexander and Nitz, 2017;Fischer et al, 2020;Mao et al, 2020;Miller et al, 2019;Powell et al, 2020;Vedder et al, 2017), and proximity to boundaries (Alexander et al, 2020;Laurens et al, 2019;van Wijngaarden et al, 2020). However, RSC neurons are also important for the memory of environmental "contexts", defined as general locations that are identifiable by invariant sensory features and that are independent of the current position or trajectory (e.g., a specific intersection, regardless of which lane one is in).…”
Section: Introductionmentioning
confidence: 99%
“…Visual landmarks influence spatial cognition [1][2][3], navigation [4,5] and goal-directed behavior [6][7][8], but their influence on visual coding in sensorimotor systems is poorly understood [6,[9][10][11]. We hypothesized that visual responses in frontal cortex control gaze areas encode potential targets in an intermediate gaze-centered / landmark-centered reference frame that might depend on specific target-landmark configurations rather than a global mechanism.…”
Section: Discussionmentioning
confidence: 99%